2019
DOI: 10.3390/molecules24030552
|View full text |Cite
|
Sign up to set email alerts
|

Ti-V-C-Based Alloy with a FCC Lattice Structure for Hydrogen Storage

Abstract: Here we report a Ti50V50-10 wt.% C alloy with a unique lattice and microstructure for hydrogen storage development. Different from a traditionally synthesized Ti50V50 alloy prepared by a melting method and having a body-centered cubic (BCC) structure, this Ti50V50-C alloy synthesized by a mechanical alloying method is with a face-centered cubic (FCC) structure (space group: Fm-3m No. 225). The crystalline size is 60 nm. This alloy may directly absorb hydrogen near room temperature without any activation proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Upon ball milling Ti and V with some carbon as a process control agent, Li et al (2019) reported a Ti 50 V 50 -10 wt% C based alloy forming a unique FCC structure with a low packing density (5.1 g cm −3 ) and a crystalline size of 60 nm. The packing efficiency of this FCC structure (52%) is comparatively lower than that reported for other structures such as FCC (74%), HCP (74%), or BCC (68%) and this possibly implies higher diffusion kinetics of H atoms as compared to hydrogen diffusion in the BCC lattice (Völkl and Alefeld, 1975;Li et al, 2019). TiVMn-and TiCrMn-based nano-alloys with FCC structure were also reported to form via mechanical milling (Li et al, 2018).…”
Section: Synthesis Methods Of Room Temperature Hydridesmentioning
confidence: 99%
“…Upon ball milling Ti and V with some carbon as a process control agent, Li et al (2019) reported a Ti 50 V 50 -10 wt% C based alloy forming a unique FCC structure with a low packing density (5.1 g cm −3 ) and a crystalline size of 60 nm. The packing efficiency of this FCC structure (52%) is comparatively lower than that reported for other structures such as FCC (74%), HCP (74%), or BCC (68%) and this possibly implies higher diffusion kinetics of H atoms as compared to hydrogen diffusion in the BCC lattice (Völkl and Alefeld, 1975;Li et al, 2019). TiVMn-and TiCrMn-based nano-alloys with FCC structure were also reported to form via mechanical milling (Li et al, 2018).…”
Section: Synthesis Methods Of Room Temperature Hydridesmentioning
confidence: 99%